Effects of Metformin Monotherapy Versus Metformin Plus SGLT-2 Inhibitor Therapy on Molecular and Cellular Inflammatory Markers in Patients with Newly Diagnosed Type 2 Diabetes Mellitus - Bennur Esen; Damla Yildiz; Ahmet Engin Atay (Journal of Clinical Medicine, 2026)
Background/Objectives: Type 2 diabetes mellitus (T2DM) is a metabolic disease characterized by insulin resistance and chronic low-grade inflammation. Tumor necrosis factor-alpha (TNF-α), interleukin-6 (IL-6), the systemic immune-inflammation index (SII), and the systemic inflammation response index (SIRI) are important markers used to evaluate inflammatory status in T2DM. This study aimed to compare inflammatory and metabolic parameters between patients receiving metformin monotherapy and those receiving metformin plus sodium-glucose cotransporter-2 (SGLT-2) inhibitor combination therapy in patients with newly diagnosed T2DM. Methods: This prospective observational study included 64 treatment-naïve patients with newly diagnosed T2DM. Patients were divided into two groups according to treatment strategy: metformin monotherapy (n = 32) and metformin plus SGLT-2 inhibitor combination therapy (n = 32). TNF-α, IL-6, SII, systemic inflammation response index (SIRI), neutrophil to lymphocyte ratio (NLR), C-reactive protein (CRP), metabolic parameters, and insulin resistance-related indices were evaluated at baseline and after six months. Baseline-adjusted multiple linear regression analyses were performed to assess between-group differences at six months, adjusting for the corresponding baseline biomarker value, baseline HbA1c, age, and sex. Results: After six months of follow-up, significant reductions in TNF-α, IL-6, glycated hemoglobin (HbA1c), and fasting plasma glucose levels were observed in both groups (p < 0.001). In baseline-adjusted analyses, the treatment-group association was not statistically significant for TNF-α (B = −26.80, β = −0.15, p = 0.213), CRP (B = 0.06, β = 0.00, p = 0.977), SII (B = −36.94, β = −0.11, p = 0.441), or NLR (B = −0.20, β = −0.18, p = 0.207). In contrast, the treatment group was associated with a lower six-month IL-6 level (B = −37.87, β = −0.31, p = 0.038; 95% CI, −73.52 to −2.23) after adjustment for baseline IL-6, baseline HbA1c, age, and sex. Serum uric acid levels were lower in the metformin plus SGLT-2 inhibitor group than in the metformin monotherapy group at six months in the unadjusted comparison (p = 0.016). However, the adjusted treatment-group association between treatment group and six-month serum uric acid levels was not statistically significant (B = −0.51, β = −0.20, p = 0.065). Conclusions: In patients with newly diagnosed T2DM, both treatment groups showed significant reductions in TNF-α and IL-6 levels over six months. After adjustment for baseline biomarker levels, baseline HbA1c, age, and sex, no significant incremental association with treatment group was detected for TNF-α, CRP, SII, or NLR, whereas a significant adjusted association was observed for IL-6. Given the observational design and physician-directed treatment allocation, the observed IL-6 association should not be interpreted as evidence of a causal anti-inflammatory effect of SGLT-2 inhibitor therapy.